Is Communism Incompatible with Religion?: Islam and Communism in Haji Misbach's Thoughts (1914-1926) - Wilandra, Syaidina Sapta (NALAR, 2024)
The article aims to explore Haji Misbach's thoughts in his writings in Medan Moeslimin newspaper regarding the harmony of communism with Islamic teachings. The study in this article uses the historical method with the stages of heuristic, source criticism, interpretation, and historiography. The primary data sources are Medan Moeslimin newspaper and various relevant archives. The data obtained is then analyzed using an intellectual history approach. This study found that when it was present in the Hindia Belanda, communism faced various other thoughts, including Islam. The communist movement at that time tried to penetrate through Sarekat Islam and made Islam the basis of its movement. At that time Haji Misbach, who was one of the Sarekat Islam figures, supported communism and saw Islam as a unity in the ideology of communism. His view differed significantly from communist figures in the West who saw religion negatively. In his writings, Haji Misbach presented communism as an analytical tool to criticize capitalism and colonialism. However, at the same time Haji Misbach also never discussed philosophically or theologically how the concept of materialism in the ideology of communism worked. Therefore, in the normative and theological realms, Misbach still believed in the truth and relevance of Islamic teachings for people's lives. Based on these findings, it can be concluded that Haji Misbach did not merely equalize or harmonize Islam with communism but also had differences in the interpretation of the ideology of communism to suit his religious life as a Muslim.